Local-province chief executive officer and managerial myopia: Evidence from China - Chen, Qian; Gao, Xiang; Niu, Shuzhen; Wang, Xiao; Wei, Qian (Frontiers in Psychology, 2022)
Managerial myopia occurs when executives value short-term benefits to the extent that firm long-run development will be obstructed. Recent studies have shown that the locality effect plays an important role in managerial myopia—local U.S. CEOs who work near their home states are less likely to behave myopically because of more effective monitoring and greater reputation concern. In an emerging market, government policies play a more important role in the strategic planning enterprises. A local CEO may have better understanding of local government’s policies thus makes less short-term decisions. This paper adds to this literature by testing whether local-province CEOs in China, i.e., the CEO’s native place or birthplace is in the same province as her company’s headquarters, are also far-sighted. Using data on 470 publicly listed non-state-owned Chinese firms from 2014 to 2018, supportive evidence has been found that non-local-province CEOs in China tend to cut R&D expenses for beating analyst forecasts, reversing earnings decline, or pursuing higher returns. This paper also confirms social capital as one mechanism of Chinese local-province CEOs behaving less myopically. This investigation also adds to the literature by revealing a new mechanism that CEO locality in China has a positive and direct bearing on how governments support corporate innovation.